Effects of dietary crude protein levels in the concentrate supplement after grazing on rumen microbiota and metabolites by using metagenomics and metabolomics in Jersey-yak - Dai, Rongfeng; Ma, Xiaoming; Dingkao, Renqing; Huang, Chun; La, Yongfu; Li, Xinyi; Ma, Xiaoyong; Wu, Xiaoyun; Chu, Min; Guo, Xian; Pei, Jie; Yan, Ping; et al. (Frontiers in Microbiology, 2023)
The nutrition level in the diet will affect the microbiome and metabolites in the rumen of ruminants. However, it is still unclear about the effects of different protein levels of supplementary diets on serum metabolites, rumen microbial community, and metabolites of Jersey-Yak (JY). The growth performance and rumen fermentation parameters of the three treatment groups varied with the supplementary diet. The dominant microbial phyla in the rumen of the three treatment groups were Bacteroidetes, Firmicutes, Kiritimatiellaeota and Proteobacteria etc. According to the analysis of diff_metabolites in serum, metabolic pathways including sphingomyelin metabolism, bile secretion, linoleic acid metabolism and histidine metabolism were significantly different before the three treatment groups. According to the analysis of diff_metabolites in rumen fluid, there were significant differences in metabolic pathways including Th17 cell differentiation, styrene degradation and bile secretion. In summary, the comprehensive use of metagenomics and metabolomics techniques to analyze the correlation between microbial communities and metabolites provides a theoretical basis for formulating a more scientific and reasonable supplementary diet in the future.